Diversity and Mollusca Distribution Patterns (Gastropoda and Bivalvia) In the North of Poncan Gadang Island, Sibolga City North Sumatera Province - Royan Saputra; Zulkifli Zulkifli; Syafruddin Nasution (Journal of Coastal and Ocean Sciences, 2020)
This research was conducted in July-August 2019 in the northern part of the Poncan Gadang Island Sibolga, North Sumatra Province. This study discusses the distribution and distribution patterns of molluscs (gastropods and bivalves) which contain species, density, and species discussed in the northern part of Poncan Gadang Island, North Sumatra Province. The method used is a survey method, where the research location is divided into 5 observation stations and each station consists of 1 transect and each transect consists of 4 maps. The results showed that the type of gastropods found in the study site consisted of 11 species belonging to 6 families. Gastropod species that are commonly found are Littorina littorea. While the type of bivalves that were found at the study site consisted of 9 species belonging to 6 families, and the bivalves species that were found were Anadara granosa. Highest density at station III in the river mouth. Various index (H ') of gastropods and bivalves in all research stations are included in the medium category. Distribution Patterns both gastropods and bivalves are distributed in groups. The index value of approved gastropod and bivalve types (Ss) can be requested types which are found to be quite the same. The substrate at the study site was approved by the sand substrate. The density of both gastropods and bivalves were not significantly different between stations.